Effects of a multiepitope covid-19 vaccine with chitosan nano-adjuvant on colon histopathology in BALB/c mice - Razky P Raharja; Endah Hamidah; Sayu P Y Paryati (ACTA Medical Health Sciences, 2025)
The COVID-19 pandemic caused by SARS-CoV-2 has posed major global challenges in infectious disease control. Vaccination remains the primary strategy to reduce morbidity and mortality; however, concerns persist regarding vaccine safety, including gastrointestinal adverse events. Multiepitope vaccines represent a promising approach to induce broader immune responses, while chitosan nanoparticles are widely studied as biocompatible adjuvants to enhance vaccine safety and efficacy. This study aimed to evaluate the histopathological effects of a multiepitope COVID-19 vaccine, with and without chitosan nanoparticles, on the colon of male BALB/c mice. A post-test-only control group design was employed using 25 male BALB/c mice, divided into five groups (n = 5 per group). Colon tissues were examined histopathologically using Hematoxylin–Eosin (H&E) staining andassessed according to the Harpaz Histological Scoring System (HSS). The results demonstrated that 100% of samples across all treatment groups exhibited an HSS score of 1, indicating mild inflammatory cell infiltration involving less than 50% of crypts without erosion or ulceration. No samples showed HSS scores of 0, 2, or 3. Due to the homogeneous distribution of histopathological scores across all groups, inferential statistical analysis could not be performed. In conclusion, administration of the multiepitope COVID-19 vaccine, either alone or combined with chitosan nanoparticles, did not induce pathological changes in the colon of BALB/c mice. These findings support the gastrointestinal safety of the vaccine formulation and its potential for further development as a safe and effective COVID-19 vaccine candidate DOI: 10.35990/amhs.v4n2.p68-76 REFERENCES Wulan D, Suwandewi A, Khatimah H. Faktor risiko penularan COVID-19 di masyarakat Diah. Jurnal Penelitian Kesehatan Suara Forikes. 2023;14(7):73–76. Aditia A. COVID-19: Epidemiologi, virologi, penularan, gejala klinis, diagnosis, tatalaksana, faktor risiko, dan pencegahan. Jurnal Penelitian Perawat Profesional. 2021;3(4):653–660. Tersedia pada: https://jurnal.globalhealthsciencegroup.com/index.php/JPPP/article/view/574/410 Kementerian Kesehatan Republik Indonesia. Vaksinasi COVID-19 Nasional. 2025. Tersedia pada: https://vaksin.kemkes.go.id/#/vaccines Wahyudi F, Nugraheni A, Margawati A, et al. Adverse events following immunization (AEFI): COVID-19 vaccine dose and characteristics in Central Java, Indonesia. Germs. 2023;13(1):40–49. Muthoharoh A, Waznah U. Survey gejala dan pengobatan yang dilakukan masyarakat Jawa Tengah pasca vaksin COVID-19. Jurnal Ilmiah Farmasi. 2024;3(3):289–296. Akaishi T, Takahashi T, Sato S, Jin X, Masamune A, Ishii T. Prolonged diarrhea following COVID-19 vaccination: A case report and literature review. Tohoku Journal of Experimental Medicine. 2022;257(3):251–259. Ajmera K, Bansal R, Wilkinson H, Goyal L. Gastrointestinal complications of COVID-19 vaccines. Cureus. 2022. Shimada T, Takada J, Baba A, et al. An elderly patient developed ulcerative colitis after SARS-CoV-2 mRNA vaccination: A case report and review of the literature. Internal Medicine. 2024;63(6):809–814. Taida T, Kato J, Ishikawa K, et al. Severe ulcerative colitis induced by COVID-19 vaccination. Clinical Journal of Gastroenterology. 2024;17(3):447–450. Weaver KN, Zhang X, Dai X, et al. Impact of SARS-CoV-2 vaccination on inflammatory bowel disease activity and development of vaccine-related adverse events: Results from PREVENT-COVID. Inflammatory Bowel Diseases. 2022;28(10):1497–1505. Ren LL, Wang YM, Wu ZQ, et al. Identification of a novel coronavirus causing severe pneumonia in humans: A descriptive study. Chinese Medical Journal (English). 2020;133(9):1015–1024. Lidiana EH, Mustikasari H, Pradana KA, Permatasari A. Gambaran karakteristik kejadian ikutan pasca vaksinasi COVID-19 pada tenaga kesehatan alumni Universitas ‘Aisyiyah Surakarta. Jurnal Ilmiah Kesehatan. 2021;11(1):11–17. Oladipo EK, Ajayi AF, Ariyo OE, et al. Exploration of surface glycoprotein to design multi-epitope vaccine for the prevention of COVID-19. Informatics in Medicine Unlocked. 2020;21:100438. Yang Z, Bogdan P, Nazarian S. An in silico deep learning approach to multi-epitope vaccine design: A SARS-CoV-2 case study. Scientific Reports. 2021;11(1):1–21. Tersedia pada: https://doi.org/10.1038/s41598-021-81749-9 Marshall JS, Warrington R, Watson W, Kim HL. An introduction to immunology and immunopathology. Allergy, Asthma & Clinical Immunology. 2018;14(Suppl 2):1–10. Tersedia pada: https://doi.org/10.1186/s13223-018-0278-1 Castrodeza-Sanz J, Sanz-Muñoz I. Adjuvants for COVID-19 vaccines. 2023:1–17. Dmour I, Islam N. Recent advances on chitosan as an adjuvant for vaccine delivery. International Journal of Biological Macromolecules. 2022;200:498–519. Schwedhelm P, Kusnick J, Heinl C, Schönfelder G, Bert B. How many animals are used for SARS-CoV-2 research? EMBO Reports. 2021;22(10):e52812. Atmojo JT, Akbar PS, Kuntari S, Yulianti I, Darmayanti AT. Definisi dan jalur penularan Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) atau COVID-19. Jurnal Pendidikan Kesehatan. 2020;9(1):57. Mudzakkir M, Risnasari N, Nugraha MFE, Mawadha SA. Upaya pencegahan penularan COVID-19 pada masyarakat Kabupaten Kediri. Kontribusi: Jurnal Penelitian dan Pengabdian kepada Masyarakat. 2021;2(1):56–65. Yüce M, Filiztekin E, Özkaya KG. COVID-19 diagnosis: A review of current methods. Biosensors and Bioelectronics. 2021;172:112752. Gorkhali R, Koirala P, Rijal S, Mainali A, Baral A, Bhattarai HK. Structure and function of major SARS-CoV-2 and SARS-CoV proteins. Bioinformatics and Biology Insights. 2021;15:1–11. Sukmana M. The pathogenesis of COVID-19 in the context of establishing a nursing diagnosis. Jurnal Kesehatan Pasak Bumi Kalimantan. 2020;3(1):21–28. Wan Y, Shang J, Graham R, Baric RS, Li F. Receptor recognition by the novel coronavirus from Wuhan: An analysis based on decade-long structural studies of SARS coronavirus. Journal of Virology. 2020;94(7):e00127-20. Mönkemüller K, Fry LC, Rickes S. COVID-19, coronavirus, SARS-CoV-2 and the small bowel. Revista Española de Enfermedades Digestivas. 2020;112(5):383–388. Achard V, Aebersold DM, Allal AS, et al. A national survey on radiation oncology patterns of practice in Switzerland during the COVID-19 pandemic: Present changes and future perspectives. Radiotherapy and Oncology. 2020;150:1–3. Elbadry M, Medhat MA, Zaky S, Kassas ME. Ulcerative colitis as a possible sequela of COVID-19 infection: The endless story. Arab Journal of Gastroenterology. 2022;23(2):134–137. Kementerian Kesehatan Republik Indonesia. Peraturan Menteri Kesehatan Nomor 23 Tahun 2021 tentang Perubahan Ketiga atas Peraturan Menteri Kesehatan Nomor 10 Tahun 2021 tentang Pelaksanaan Vaksinasi dalam Rangka Penanggulangan Pandemi COVID-19. Jakarta: Kemenkes RI; 2021. Saleh A, Qamar S, Tekin A, Singh R, Kashyap R. Vaccine development throughout history. Cureus. 2021;13(7):e16693. Shahcheraghi SH, Ayatollahi J, Aljabali AAA, et al. An overview of vaccine development for COVID-19. Therapeutic Delivery. 2021;12(3):235–244.